Entre giras e batuques: o Marabaixo em sala de aula - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2025)
This study addresses the concepts related to aspects of Marabaixo performance, highlighting it as a relevant manifestation for classroom teaching through its oralitura. The analysis of this manifestation as literature stemmed from our experience in a higher education course, where we deepened discussions on the practice and realized how much Marabaixo, as literature in the classroom, had been absent from our basic education. Therefore, we conducted research in educational documents, such as the Base Nacional Comum Curricular (BNCC) and the Referencial Curricular Amapaense (RCA), which revealed the lack of integration of Afro-Brazilian and Afro-Amapaense literatures within the artistic-literary field of high school. In this way, we produced a curation that presents the components of Marabaixo as archives of memory, resistance, and identity, aiming at the inclusion of this literature in the classroom through introductory teaching. This enables teachers to use the curated archives in their pedagogical practice and students to assimilate Marabaixo in a meaningful way. For this purpose, we developed an analysis based on the concepts of Foucault, Cosson, Martins, Bosi, Pereira, and Zumthor.
Keywords: Base Nacional Comum Curricular (BNCC); Literatura afro-amapaense; Patrimônio cultural imaterial - Marabaixo; Identidade cultural; CNPQ::LINGUISTICA, LETRAS E ARTES::LETRAS; ODS 10 – Redução das desigualdades; ODS 11 – Cidades e comunidades sustentáveis; ODS 4 – Educação de qualidade; ODS 5 – Igualdade de gênero